Covid-19 Home Surveillance for Self-quarantine Monitoring System using IoT - Mohamad, Muhammad Zarim; Zainal Abidin, Zuhairiah (Evolution in Electrical and Electronic Engineering, 2022)
In recent years, the Internet of things (IoT) has developed as a new research topic in a range of academic and industrial fields, notably in healthcare. The IoT revolution is reshaping modern healthcare systems, with implications for technology, economics, and society. Traditional healthcare systems are evolving into more personalized systems that simplify diagnosing, treating, and monitoring patients. Because of the increased likelihood of COVID-19 in the current pandemic, patients must be tracked at various phases of COVID-19. IoT devices can remotely track patients’ locations in connection to their treatments and authority stay-at-home orders during this period. The purpose of this project is to develop a monitoring system for a home surveillance system to monitor the movement and location of the COVID-19 patient. This project’s development used an IoT-based implementation that can aid in tracking the patient’s whereabouts utilizing a GPS tracking system and monitoring their movement. The Cloud Firebase Database may store and access real-time data on the location and information of the patient. This application also has an alert notification mechanism that alerts users when the geofence radius is exceeded. An android-based application with a GPS tracking system based on the IoT has been successfully developed, allowing patients’ data and information to be accessible via the Cloud Firebase Database.